PREPARATION AND CHARACTERISTICS OF PACIFIC CODFISH (Gadus macrocephalus) MYOFIBRIL FOR SURIMI - Agustia Dwi Pamujiati; Yuli Witono; Nina Lisanty (Food ScienTech Journal, 2020)
Myofibril is contributing to gel-forming. Every species of fish have different myofibril concentration. Pacific codfish has white flesh which is expected to make surimi. The objective of this research was to analyze the characteristics of surimi prepared from Pacific codfish myofibril (SPM). The method of this research was used ionic strength by using NaCl. The observe parameters of this research were protein solubility, color, microstructure, molecular weight,and texture.the results showed that SPM have 3-dimensional network with rigid and porous structure than other surimi gels. The major molecular weights were 150 kDa (zetalin) and 40 kDa (tropomyosin). The hardness, cohesiveness and adhesiveness of SPM were 0.071338 N/cm2, 0.259 gf/sec and 116 gf.mm respectively. These results were shown that Pacific codfish was suitable to be used as surimi raw material because it can make a good gel to form surimi.